Evaluation of the Relationship between Renal Dysfunction (Urea and Creatinine Levels) and Cardiac Pathology Indicators in Diabetic Patients - Muhialdeen, Omaima AbdulKareem (Journal of Science in Medicine and Life, 2025)
The current study was conducted in order to find out the elevated levels of urea and creatinine in the blood serum of diabetics are considered an indicator of cardiovascular disease. city. The study was designed on 60 person in August 2025 at Kirkuk City, 20 patients with diabetes without cardiovascular disease, 20 diabetic patients with cardiovascular disease who were hospitalized to Kirkuk General Hospital and 20 person as control. The patients were 30 men and 30 women, with ages ranging from 50 to 70. Information such as age, sex, weight, blood pressure, illness symptoms, smoking, and diet adherence were collected and entered into a questionnaire created specifically for this purpose. Tests for renal function (creatinine and urea) and fasting blood sugar were performed in the hospital lab. According to the findings, patients had higher than usual amounts of sugar, urea, and creatinine—all of which are markers of the risk of cardiovascular disease.